2009
DOI: 10.1111/j.1755-3768.2009.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intraocular pressure elevation after pupillary dilation in exfoliation syndrome

Abstract: . Purpose:  To determine the effect of pupillary dilation on intraocular pressure (IOP) in normotensive patients with exfoliation syndrome (XFS). Methods:  Patients with XFS were enrolled in this prospective trial. All eyes were untreated, had no previous laser or operative surgery and were normotensive with full visual fields and open angles. IOP was measured before dilation and hourly for four consecutive hours after dilation with tropicamide 1% and phenylephrine 2.5% eyedrops. Results:  Twenty‐five eyes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
3
13
1
2
Order By: Relevance
“…Shaw & Lewis and Siam et al, also reported higher post dilatation IOPs but their studies included patients with glaucoma [16,33]. Other studies with similar results were those of Hung et al, and Shihadeh et al, but these studies were on children and patients with pseudoexfoliation respectively [17,19]. On the other hand, Pukrushpan et al, reported no significant difference in mean IOP pre and post dilatation even though their study population was similar to that of this study [24].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Shaw & Lewis and Siam et al, also reported higher post dilatation IOPs but their studies included patients with glaucoma [16,33]. Other studies with similar results were those of Hung et al, and Shihadeh et al, but these studies were on children and patients with pseudoexfoliation respectively [17,19]. On the other hand, Pukrushpan et al, reported no significant difference in mean IOP pre and post dilatation even though their study population was similar to that of this study [24].…”
Section: Discussionsupporting
confidence: 69%
“…Pupillary dilatation for dilated fundus examination (diagnostic mydriasis) is a very important aspect of ophthalmic practice. Diagnostic mydriasis has the ability to cause both ocular and systemic effects [14][15][16][17][18][19][20][21][22][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei bis zu 30 % dieser Patienten ist ein signifikanter Druckanstieg feststellbar, wobei Patienten mit PEX-Glaukom und PEX-Syndrom (PEX: Pseudoexfoliation) häufiger betroffen sind als Patienten mit primär chronischem Offenwinkelglaukom [22]. Bei Patienten mit PEX-Syndrom kann ein früher leichter Druckanstieg nach Mydriase (1 h nach Applikation) Vorbote eines zeitlich verzögerten stärkeren Druckanstiegs (2-3 h nach Applikation) sein, der durch eine Pigmentausschüttung nach Mydriase ausgelöst wird [23]. Gerade bei Patienten mit bereits stärkerer Optikusschädigung sollte auf dieses Phänomen geachtet werden.…”
Section: Pupillenwirksame Medikamenteunclassified
“…Los pacientes con GPEX presentan un mayor riesgo de sufrir picos de incremento de la PIO transitorios tras la dilatación pupilar debido a la dispersión de partículas de pigmento y de material pseudoexfoliativo en la cámara anterior que se produce tras la instilación tópica de midriáticos. La máxima elevación de la PIO, que puede alcanzar hasta los 30 mmHg sobre la PIO basal del paciente, se alcanza de 2 a 3 horas tras la dilatación pupilar y tarda de 10 a 15 horas en volver a normalizarse [163].…”
Section: 1-glaucoma Secundario De áNgulo Abiertounclassified